The development of strong career learning environments : the project 'Career Orientation and Guidance' in Dutch vocational education - Draaisma, Aniek [Verfasser]; Meijers, Frans [Verfasser]; Kuijpers, Marinka [Verfasser] (My University, 2018)
"Schools are increasingly acknowledging their responsibility to guide students in their career development. However, the guidance that is provided in the Netherlands, as well as in other Western countries, focuses for the most part on helping students towards their academic achievement, and not on helping them to develop competencies to manage their own career. In order to promote this type of career guidance, 37 secondary vocational schools in the Netherlands participated in a project that offered a training programme, aiming to teach teachers how to conduct career dialogues with students. The programme offers expert guidance to integrate a dialogical approach to career guidance and a more enquiry- and practice-based curriculum in the school's vision and policy. In this article, the results of semi-structured interviews with 50 teachers who participated in the project are presented. These interviews were conducted right after the start of the project, to study how teachers perceive the initial situation regarding career development in their schools, as well as their perception of the initiated plans and ambitions for development, both in their own learning environment and the learning environment of their students." (Author's abstract, BIBB-Doku)
Keywords: L 5 Beratung & Orientierung; G 2.4.4 Biografiegestaltung; G 1.3.3 Bildungs- & Erwerbsbiografien; P 3.2 Lehrpersonal; Berufsberatung; Berufsorientierung; Biografiegestaltung; Berufswegplanung; Lehrerbildung; Niederlande